2016
DOI: 10.3390/ijms17071070
|View full text |Cite|
|
Sign up to set email alerts
|

Involvement of the Interleukin-23/Interleukin-17 Axis in Chronic Hepatitis C Virus Infection and Its Treatment Responses

Abstract: Interleukin-23 (IL-23) and its downstream factor IL-17 are the key cytokines involved in immune and inflammatory response in chronic liver diseases. This study aimed to investigate the role and molecular mechanisms of the IL-23/Th17 axis in chronic hepatitis C virus (HCV) infection, and the efficacy of IL-23/Th17 modulation in response to anti-HCV therapy. Sixty-six HCV-infected patients and 20 healthy controls were enrolled. The patients received PegIFNa-2a and ribavirin therapy for at least 48 weeks. The pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…[14] The differences between the means of the patients and control groups (Z = -2.139) were significant at (p<0.05) which is most likely due to the important role that IL 17 plays during the chronic viral infection in indicating liver damage as explained previously in the literature review chapter. [12] Results also showed a highly significant decrease (P <0.01) in trimmed mean of IL-17 serum levels in HBV patients when compared to HCV patients group (Z = -4.321). In agreement, Sousa [15] found the mean of IL-17 serum level in HCV patients to be (96.8ng/L) while Du [16] found the mean of Il-17 in HBV patients to be (38.9 ng/L), which is lower than in HCV cases.…”
Section: Levels Of Interleukin 17 (Ng/l) In Studied Groupsmentioning
confidence: 73%
See 1 more Smart Citation
“…[14] The differences between the means of the patients and control groups (Z = -2.139) were significant at (p<0.05) which is most likely due to the important role that IL 17 plays during the chronic viral infection in indicating liver damage as explained previously in the literature review chapter. [12] Results also showed a highly significant decrease (P <0.01) in trimmed mean of IL-17 serum levels in HBV patients when compared to HCV patients group (Z = -4.321). In agreement, Sousa [15] found the mean of IL-17 serum level in HCV patients to be (96.8ng/L) while Du [16] found the mean of Il-17 in HBV patients to be (38.9 ng/L), which is lower than in HCV cases.…”
Section: Levels Of Interleukin 17 (Ng/l) In Studied Groupsmentioning
confidence: 73%
“…It was also suggested that antiviral treatment lowers the levels of IL-17 in patients' serum. [12] , [13] This decrease in IL-17 seems to favor the survival of subjects under treatment. [14] The differences between the means of the patients and control groups (Z = -2.139) were significant at (p<0.05) which is most likely due to the important role that IL 17 plays during the chronic viral infection in indicating liver damage as explained previously in the literature review chapter.…”
Section: Levels Of Interleukin 17 (Ng/l) In Studied Groupsmentioning
confidence: 97%
“…In contrast, virus-specific T H 17 cells were correlated with liver injury and inflammation, but T H 17 quantity could not be linked to effective viral clearance. Furthermore, IL-23 and IL-17 levels in HCV-infected patients were elevated, and IL-23 therapy was reported to modulate the antiviral response by preferentially promoting T H 17 immune cells ( Meng et al, 2016 ). In a course of HCV infection, T Reg cells were mainly found in necro-inflammatory liver areas to inhibit the effector CD8 T cell response, which is the main cause of liver damage in HCV and hepatitis B virus (HBV) infection.…”
Section: The T H 17/t Reg Cell mentioning
confidence: 99%
“…Alteration in the interleukin-23 (IL-23)/Th17 signaling axis has been suggested as an important trigger for chronic inflammation [66,67,68,69,70,71,72]. Briefly, this pathway corresponds to the polarization of naïve CD4 positive cells towards a T-helper cell (Th17) phenotype, associated with by the predominant production of IL-17 and IL-22.…”
Section: How the Gut Microbiome Affects Asmentioning
confidence: 99%